2014
DOI: 10.1161/circulationaha.114.009690
|View full text |Cite
|
Sign up to set email alerts
|

Are Hemodynamics Surrogate End Points in Pulmonary Arterial Hypertension?

Abstract: Background While frequently assessed in trials and clinical practice, hemodynamic response to therapy has never been validated as a surrogate endpoint for clinical events in pulmonary arterial hypertension (PAH). Methods and Results We performed a patient-level pooled analysis of four randomized placebo-controlled trials to determine if treatment-induced changes in hemodynamic values at 12 weeks accounted for the relationship between treatment assignment and the probability of early clinical events (death, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 51 publications
(54 reference statements)
0
49
0
Order By: Relevance
“…The hemodynamic response to AN would have been of interest; however, the requirement for multiple right heart catheterizations on otherwise stable, treated patients would have rendered the trial infeasible. In addition, we have shown that short-term hemodynamics are not adequate surrogate endpoints in PAH trials, so that conclusions based on early hemodynamic findings (or lack thereof) might be in error (42). We also did not measure E2 metabolites, which may have been of interest based on previous studies (25,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…The hemodynamic response to AN would have been of interest; however, the requirement for multiple right heart catheterizations on otherwise stable, treated patients would have rendered the trial infeasible. In addition, we have shown that short-term hemodynamics are not adequate surrogate endpoints in PAH trials, so that conclusions based on early hemodynamic findings (or lack thereof) might be in error (42). We also did not measure E2 metabolites, which may have been of interest based on previous studies (25,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have found that while changes in these measures were associated with outcomes in PAH clinical trials (as in prior observational studies), the drug-induced changes (compared with placebo) explained very little of the variances in outcomes [11][12][13][14]. At most, the changes in 6MWD and pulmonary vascular resistance respectively explained only 22% and 14% of the effect of treatment on clinical events at 12 weeks, falling short of the desired 50% mark and suggesting that they are not valid surrogates for short-term outcomes.…”
mentioning
confidence: 55%
“…Therefore, surrogate measures come into place. VENTETUOLO and KAWUT correctly emphasise that adequate validation of surrogate measures is crucial and they have demonstrated that this has not been done properly for many of the clinical endpoints or treatment targets that have been proposed for adult patients with PAH [4][5][6][7]. In our study in children with PAH, we identified three intermediates in which therapy-induced changes predicted comparable directional changes in the ultimate outcome: survival [1,8].…”
Section: From the Authorsmentioning
confidence: 83%
“…Kawut depreciate the value of clinical end points in adults with PAH, requires some considerations. Recent surrogate end point validation studies in adults [4][5][6][7] evaluated therapy-induced changes in relation to composites of "soft" clinical events (including hospitalisation, clinical worsening and escalation of therapy) that have not undeniably demonstrated a correlation with the hard outcome, survival. Furthermore, analyses had to be restricted to the short duration of clinical trials (mostly 12 weeks).…”
Section: From the Authorsmentioning
confidence: 99%
See 1 more Smart Citation